2021
DOI: 10.4103/lungindia.lungindia_540_20
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous posterior lung herniation

Abstract: Intercostal lung hernias are uncommon and usually a consequence of trauma or surgery. True spontaneous lung hernias are extremely rare, with only 51 cases identified over the past four-and-half decades. We report a case of nontraumatic chest wall ecchymosis secondary to spontaneous posterior-lateral lung herniation followed by a review of the literature. Interesting radiographic images are presented. The pathophysiology and therapeutic options of this condition are discussed. The case highlights that advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…First described in 1499, the pulmonary hernia is characterized by the protrusion of the lung, including parenchyma and pleura through a defect in the chest wall 4,5 . The classical features of pulmonary hernias include visible herniation of the chest wall, localized chest pain and flank ecchymosis 1,2,6 . Most lung hernias occur in the context of trauma or post‐operatively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First described in 1499, the pulmonary hernia is characterized by the protrusion of the lung, including parenchyma and pleura through a defect in the chest wall 4,5 . The classical features of pulmonary hernias include visible herniation of the chest wall, localized chest pain and flank ecchymosis 1,2,6 . Most lung hernias occur in the context of trauma or post‐operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous pulmonary hernias due to coughing occur owing to dramatically increased intrathoracic pressure causing damage to the chest wall. Risk factors include male gender, obstructive airways disease (COPD/asthma), smoking status, steroid use and obesity 1,2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, increasingly more cases of spontaneous lung hernias have been reported in the literature during the last decade [1,2,7,11,[16][17][18][19]. Ugolini et al reported five patients, all of which were males with a median age of 68 years [2].…”
Section: Diagnosis Of Lung Herniasmentioning
confidence: 91%